Adolescent Sexual Assault and the Medical and Nonmedical Use of Prescription Medication - Young, Amy (2011)
Previous research has documented an association between sexual victimization and prescription medication use among adults. The purpose of this study was to determine whether such a relationship was present for adolescent girls when considering sexual victimization by a peer and the use of four drug classes for medical and nonmedical reasons. The study was based on a secondary analysis of a cross-sectional Web-based, self-administered survey of female students from a middle and high school (n = 490). As predicted, sexual victimization increased the likelihood of non-medical prescription medication use of opioid analgesics and sedative medication, although these relationships varied based on the severity of sexual assault. Findings are discussed in light the importance of increasing awareness among health professionals, researchers, and the wider community of the increased risk for prescription medication abuse among adolescent girls who have a history of sexual violence.